The Representation of Dataveillance in Visual Media : Subjectification and Spatialization of Digital Surveillance Practices - Hennig, Martin; Piegsa, Miriam; Justus Liebig University Giessen (My University, 2018)
Surveillance as a practice of observation is connected to metaphors that stress optical aspects referring to photographic or filming techniques. For example, films that deal with surveillance often make statements about the quality of images obtained through surveillance, and thereby influence the perception of film itself as a visual medium. However, the current ubiquity of surveillance as a social-ordering process is mainly based on the architecture of technologies designed to allow for surveillance as a form of data collection, which is known as dataveillance. Our main focus here is to explore the representation of dataveillance in visual media despite the actual de-visualization of digital surveillance practices. We carve out an analytical framework that locates some of the rhetoric of dataveillance within visual media (film, documentary, computer games) by determining dominant cultural interpretations. In doing so, we investigate the extent to which digital surveillance is visually spatialized and subjectivized, and how these strategies vary in different manifestations.
Keywords: dataveillance; documentary; gaming; surveillance culture; surveillance film; ddc:300